Revisiting the linkage between financial inclusion and economic growth: Time series evidence from Vietnam - Hye, Qazi Muhammad Adnan (Edelweiss Applied Science and Technology, 2022)
Financial inclusion has played a key role in encouraging the development of financial sectors in recent decades. Only a few studies, however, have looked at the linkage between financial inclusion and economic growth. This study examines the impact of financial inclusion on economic growth in Vietnam, utilizing data spanning the period from 2001 to 2021. The study uses composite risk, trade openness, and government expenditures as control variables. The study follows the access to finance theory, which suggests that access to financial services such as credit, savings, and insurance can help promote economic growth and development. The nexus between financial inclusion and economic growth has never been examined in the case of Vietnam, which represents a greater share of global trade and income. Moreover, this study uses trade openness, government expenditures, and the composite risk index as control variables in the empirical model. Hence, the study contributes to the existing literature in some meaningful ways. This study employs the FMOLS method to estimate the long-run coefficients of financial inclusion, trade openness, composite risk, and government expenditures. According to the findings, financial inclusion boosts economic performance. On the contrary, composite risk is negatively related to economic growth. The results of this study suggest that Vietnam must implement policies to improve financial inclusion so as to enhance its economic growth.